Time-frequency volatility spillovers across the international crude oil market and Chinese major energy futures markets: Evidence from COVID-19. (August 2022) - Li, Jingyu; Liu, Ranran; Yao, Yanzhen; Xie, Qiwei
Abstract: This study investigates the impact of the recent COVID-19 pandemic on the time-frequency volatility spillovers across the international crude oil market and Chinese major energy futures markets. In addition to the Chinese crude oil market, six other major energy futures markets in China are also considered. Volatility spillover networks are constructed based on the generalized forecast error variance decomposition in the frequency domain. The results demonstrate that the outbreak of COVID-19 strengthened the total volatility spillover across these markets. Interestingly, the volatility spillovers from the international crude oil market to China's markets were found to be overall strong in the long term and to have increased substantially during the pandemic. However, the spillovers across the domestic markets were found to dominate in the short term, even with the occurrence of the pandemic and crude oil price turbulence. The findings suggest that policymakers and investors should be cautious about the diverse impacts of the pandemic at multiple scales. Highlights: We consider the effect of OVX on the Chinese energy markets during COVID-19. We provide evidence for the connectedness of China's major energy futures markets. The COVID-19 and the turmoil of oil strengthen the risk spillovers of the markets. The OVX's spillovers to China's energy futures markets are strong in the long-term. The spillovers across China's energy futures markets dominate in the short-term.